NITROGEN-CONTAINING HETEROCYCLE DERIVATIVES, PHARMACEUTICAL COMPOSITIONS, AND METHODS OF USE THEREOF AS ANTIVIRAL AGENTS - ARIMILLI, MURTY, N; ROTHLEIN, ROBERT; ANDREWS, ROBERT, C; ALTEL, TALEB, H; MJALLI, ADNAN, M., M; COOPER, JEREMY, T (2008)
The present application provides nitrogen-containing heterocycle derivatives that are antiviral compounds that may be useful in the treatment of a viral infection. Compounds of Formula (I) and pharmaceutical compositions comprising a compound of Formula (I) may be administered to a subject for antiviral therapy or prophylaxis. Formula: (I) L'invention concerne des dérivés hétérocycliques contenant de l'azote qui sont des composés antiviraux qui peuvent être utiles dans le traitement d'une infection virale. Les composés de la formule (I) et Les compositions pharmaceutiques comprenant un composé de la formule (I) peuvent être administrés à un sujet pour une thérapie antivirale ou une prophylaxie.